Emotional intelligence and leadership effectiveness among nurse managers in selected military hospitals in Metro Manila - Barroga, Junalyn A.
The continuous and unprecedented changes in the healthcare environment illustrated by human resource crisis and increasing consumer demands for a more relationship-centered and service-oriented health care system, had been the critical factors that continually shape the evolving role of the qualified nurse. Although technical expertise and critical thinking skills are invaluable, emotional intelligence abilities that help develop and enhance interpersonal skills, innovativeness, and effective leadership are equally important for the successful and effective delivery of care services, and creating satisfied customers for the organization. More than ever, the unique position of the nurse manager within the health care organization compels him or her to answer the call to transformation and creation of a new culture that integrates emotional intelligence into its very core.